Assessing the role of "Jalari" women in livelihoods and aquatic resources management in Phewa Lake, Pokhara, Nepal - Nepal, Agni Prasad; Gallardo, Wenresti G.; Bart, Amrit N.; Doneys, Philippe; Bhujel, Ram C.; Berg, Hakan (Pathum Thani, Thailand : Asian Institute of Technology, 2008)
A study was conducted on 44 of 79 households of Jalari community residing around Phewa Laketo assess the role of women in livelihood strategies and their initiatives for aquatic resources conservation and management in this lake. There is significant involvement of Jalari women in occupational activities, where they contribute about 41% of the work, related to aquaculture and fisheries in addition to their household chores and this contribution is as much as men (P>0.05). Almost all (about 98%) Jalaris are satisfied with their present job. However, about 59% females are interested in part-time/side works, such as tailoring and/or embroidery for additional income, whereas majority (64%) of males are not interested. Majority (86%) of women in this community do not feel their present work is overload. Lack of education is one of the hindrances for the development of Jalari community, where only about 32% adult women are literate. However almost all girls below 16 years are attending school, so overall women literacy has been in increasing. Women have a main role of keeping money but women consult husband on the matter of using it and cases of large items purchase. Since 2004 Jalari women are also involved in restocking fingerlings of native fish species such as Rohu (Labeo rohita), Mrigal (Cirrhinus mrigala), Catla (Catla catla), Sahar (Tor sp.), and exotic species such as Bighead carp (Aristichthys nobilis) and Silver carp (Hypophthalmichthys molitrix) into the lake and their contribution is around 4% of the total restocked fish species in the past four-years. More than 72% of Jalari women expressed their concerns about conservation of high value native species. Most importantly their attention has been focused on the conservation of Sahar fish. Unintended introduction of tilapia (Oreochromis niloticus) and African catfish (Clarias gariepinus) is a concern to biodiversity of the lake. Women have a good understanding and interest for conserving the lake resources, biodiversity and maintaining beauty of the lake. Almost all Jalari respondents (about 96%) agreed that environmental problem is severe in Phewa Lake and problems are mainly caused by weed infestation, pollution, silt deposition and encroachment of original boundary. In the case of capability of women to run projects, 80% respondents have confidence on women that they would be able to show a positive impact in resources conservation and they are highly capable (P<0.05) to perform the works if they get opportunity. Likewise, works performed by women for resources conservation and participation in social works are highly effective (77.3% and 84.1% respondents respectively, P<0.05).
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Aquaculture and Aquatic Resources Management, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 2008
Keywords: Aquatic resources -- Nepal -- Pokhara -- Management; Jalaris -- Nepal -- Pokhara; Women in development -- Nepal -- Pokhara